2021
DOI: 10.3390/biomedicines9081049
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Odontoblast-like Differentiation from Dental Pulp Stem Cells through Increase of β-Catenin/p-GSK-3β Expression by Low-Frequency Electromagnetic Field

Abstract: Odontoblasts produce proteins that form the dentinal extracellular matrix, which can protect the dental pulp from external stimuli and is required for tooth regeneration. This study showed that a pulsed electromagnetic field (PEMF) can regulate cell metabolism and induce cell differentiation. This study determined the frequency of PEMF that is effective for odontoblast differentiation. Human dental pulp stem cells (hDPSCs) were cultured in odontoblast differentiation medium containing dexamethasone, BMP2, TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Several studies have shown that YAP signaling plays an important role in osteogenesis and mechano-transduction. , Others have claimed that cytoskeletal reorganization activates β-catenin. For example, Sen et al found that dynamic strain induced actin restructuring, nuclear transport of G-actin, and nuclear access of β-catenin, and DPSCs on high rough electrospun polystyrene nanofibrous (PSF) matrix expressed higher levels of Wnt3a, nuclear β-catenin, and DSPP .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that YAP signaling plays an important role in osteogenesis and mechano-transduction. , Others have claimed that cytoskeletal reorganization activates β-catenin. For example, Sen et al found that dynamic strain induced actin restructuring, nuclear transport of G-actin, and nuclear access of β-catenin, and DPSCs on high rough electrospun polystyrene nanofibrous (PSF) matrix expressed higher levels of Wnt3a, nuclear β-catenin, and DSPP .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate calcified minerals, the alizarin red was dissolved for 16 h with 5% 2-isopropanol (Sigma-Aldrich) and 10% acetic acid solution (Sigma-Aldrich). Absorbance was at 550 nm in a microplate reader spectrophotometer [ 15 , 16 ]. The calcium deposition was evaluated by performing a Von Kossa stain using a 5% silver nitrate (Sigma-Aldrich) solution under ultraviolet light for 20 min, followed by a 5% sodium thiosulphate (Sigma-Aldrich) solution for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…These systems can typically contain different coil geometries that act as passive elements for magnetic field generation such as solenoids (Han et al, 2018;Sanie-Jahromi and Saadat, 2018;Costantini et al, 2019;Samiei et al, 2020;Mansoury et al, 2021;Salek et al, 2021;Maleki et al, 2022;Mansoury et al, 2022), circular (Yuan et al, 2018;López et al, 2019;García-minguillán et al, 2020;Xu et al, 2020;Yuan et al, 2020;Asadian et al, 2021) or square (Consales et al, 2018;Sun et al, 2018;Zuo et al, 2020;Elexpuru-Zabaleta et al, 2023;Lazzarini et al, 2023) coils arranged in different configurations, such as the Merrit configuration (Kirschvink, 1992) or the Helmholtz configuration (Kirschvink, 1992;López et al, 2019;García-minguillán et al, 2020;Xu et al, 2020;Asadian et al, 2021;Cios et al, 2021;Lim et al, 2021). The latter is one of the most popular configurations for exposing cell cultures or small animals to ELF-EMF (López et al, 2019;Garcíaminguillán et al, 2020;Xu et al, 2020;Asadian et al, 2021;Cios et al, 2021;Lim et al, 2021). In particular, the use of circular coils arranged in a Helmholtz configuration is one of the most widely used worldwide (Luo et al, 2016;Villarini et al, 2017;Ross et al, 2018;López et al, 2019;…”
Section: Introductionmentioning
confidence: 99%
“…The latter is one of the most popular configurations for exposing cell cultures or small animals to ELF-EMF (López et al, 2019;Garcíaminguillán et al, 2020;Xu et al, 2020;Asadian et al, 2021;Cios et al, 2021;Lim et al, 2021). In particular, the use of circular coils arranged in a Helmholtz configuration is one of the most widely used worldwide (Luo et al, 2016;Villarini et al, 2017;Ross et al, 2018;López et al, 2019;Yao et al, 2019;García-minguillán et al, 2020;Asadian et al, 2021;Cios et al, 2021;Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%